Bibliometric Analysis of the 2019–2023 Leadership Mapping of Indonesia's Chief Schools: Chief's leadership mapping - Hutagalung, Cerli Elperida; Santo, Heru; Susanto, Teguh Trianung Djoko (International Education Trend Issues, 2024)
The leadership difficulties faced by school principals are becoming more complicated in the context of globalization and the fourth industrial revolution. In addition to managerial skills, transformative leadership, digital leadership, and learning leadership are also desired qualities for principals. As such, examining the leadership styles of today's principals in schools is crucial. The opportunities and difficulties experienced by school principals can be summarized in this report, along with trends in principled leadership. Newness: Using bibliometric analysis as support, this study will examine the most recent research themes from 2019 to 2023. Approaches to Research: On January 2, 2024, Google Scholar was used to conduct the search. Specifically in Indonesian abstracts, keywords, and title search terms, the phrase "principal leadership"